Analyzing the Relationship between Financial Digitalization and Investment Opportunity set - A. H. Hindi Al-Ali; S. S. Sarhan Al-Ruaziq (Финансы: теория и практика, 2025)
The purpose of the study is to reveal the nature of the relationship between financial digitalization approved by nonfinancial institutions such as communication companies (mobile phones) and the size of growth in their investment opportunities. The study sought to analyze the volume of financial exchange resulting from some banking activities adopted by the aforementioned companies through their operations Operational, in a step to facilitate the lives of its customers by providing electronic financial wallets licensed by the Central Bank of Iraq that allow them to deposit, withdrawal and transfer funds. In the current study, the comparative analytical approach was adopted for the study sample which are the two companies: Asia Cell and Zain Iraq, for the period from (January 2018 to December 2022), and the necessary data was obtained from the statistical publications of the Central Bank of Iraq, and the data published in Iraq Stock Exchange market, and this data was processed financially according to mathematical equations to measure the variables of the study, and statistically through the program (SPSS-V: 22) to reach the desired goals. The study reached a number of results, the most important of which is the significant increase in the growth of digitalization of banking business adopted by the two communication companies (study sample) during the specified period despite the clear discrepancy between them, as well as the clear growth in increasing their investment opportunities for the same period. The most important recommendations were the need to work on increasing the banking financial services provided by these companies through their electronic applications, in addition to encouraging mobile phone users to benefit from the banking services provided to them through the electronic applications approved by them, which are (Zain Cash & Asia Hawala).